Dynamics of scattering and dissociative adsorption on a surface alloy: H2/W(100)-c(2x2)Cu - Batista, Maria Natalia (2011)
H_2 scattering and dissociative adsorption on the W(100)c(2x2)Cu surface alloy is studied based on DFT calculations. A strongly site dependent reactivity is observed in line with results obtained  for the density of states projected onto the W and Cu atoms of the topmost layer. H_2 dissociation  on a defect free terrace of W(100)c(2x2)Cu is found to be a non-activated process like on  W(100), despite the reduction of the number of energetically accessible dissociation pathways at  low impact energies due to the presence of Cu atoms. A prominence of dynamic trapping and a reduction of the eﬃcacy of trapping to promote dissociation is also veriﬁed, leading to a  decrease of the initial sticking probability as a function of the molecular impact energy, in  qualitative agreement with experimental ﬁndings. The heterogeneous reactivity is also evidenced  by two diﬀerent kinds of reﬂection events at low energies. Its combination gives rise to a broad  specular peak superimposed on a cosine-like angular distribution of scattered molecules which is  in good agreement with available experimental data.